The Rise of a Middle Class in East and Southern Africa: Implications for Food System Transformation. (15th July 2015) - Tschirley, David; Reardon, Thomas; Dolislager, Michael; Snyder, Jason
Abstract: We show five points regarding the middle class in developing East and Southern Africa: (1) 55 per cent of the region's middle class—37 per cent of the 'non‐vulnerable' middle class—is rural; (2) 61–83 per cent of the middle class's food is purchased; (3) processed food occupies 70–80 per cent of the class's food expenditure, with similar shares in urban and rural areas; (4) perishable products account for 44–55 per cent of the class's expenditure. Policy attention to processing and to food products 'beyond‐grains' thus needs to be 'mainstreamed'; and (5) the import share of food expenditure does not rise with income in urban areas. © 2015 The Authors. Journal of International Development published by John Wiley & Sons, Ltd.